College Algebra 7th Edition

Published by Brooks Cole
ISBN 10: 1305115546
ISBN 13: 978-1-30511-554-5

Chapter P, Prerequisites - Chapter P Review - Exercises: 63

Answer

$(x-3)(x^2+3x+9)$

Work Step by Step

Since $27=3^3$, the given expression is equivalent to: $=x^3-3^3$ The expression above is a difference of two cubes. Factor using the formula $a^3-b^3=(a-b)(a^2+ab+b^2)$ with $a=x$ and $b=3$ to obtain: $=(x-3)(x^2+x(3) + 3^2) \\=(x-3)(x^2+3x+9)$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.